Language Accommodation in Speak Communities in Banyumas District - Gita Anggria Resticka; Erwita Nurdiyanto; Gigih Ariastuti Purwandari (Badan Pengembangan dan Pembinaan Bahasa, 2023)
Language diversity gives rise to language phenomena (language contact, language borrowing, language shift, language maintenance and language accommodation). Even though Indonesian appears to be the state or unified language, the role of regional languages and foreign languages (English) is quite influential in social life. The purpose of this research is to provide information regarding trends in linguistic phenomena that will occur in the languages spoken in Banyumas Regency. This research also aims to determine the communication strategy and level of accommodation of the speech community in Banyumas Regency. In addition, this research aims to identify diversity in the use of Indonesian, regional languages and foreign languages based on the characteristics of respondents in the areas used in Banyumas Regency. Another aim is to identify which social communities in each language community are more dominant in linguistic adaptation while other communities are not dominant. Identifying whether there are differences in the tendency to make linguistic adaptations between speech communities that are prone to conflict (disharmony) and speech communities that are not susceptible to social conflict (harmony). Data collection used listening techniques and depth interviews. Data analysis using interactive models. The results of this research indicate that there are challenges to linguistic adaptation of speech communities in Banyumas Regency which are related to differences in language, culture and communication styles that exist with different backgrounds. Then, there is a linguistic adaptation strategy for the speech community in Banyumas Regency which is related to communicative competence. The language accommodation of the Banyumas spoken community towards Indonesian is very accommodating, towards mother tongue it is also accommodating, but towards second regional languages and foreign languages it is not accommodating. AbstrakKeberagaman bahasa memunculkan fenomena bahasa (kontak bahasa, peminjaman bahasa, pergeseran bahasa, pemertahanan bahasa dan akomodasi bahasa). Meskipun bahasa Indonesia tampil menjadi bahasa negara atau bahasa persatuan, tetapi peran bahasa daerah dan bahasa asing (Inggris) cukup berpengaruh di dalam kehidupan bermasyarakat. Tujuan penelitian ini adalah sebagai informasi mengenai kecenderungan fenomena kebahasaan yang akan terjadi pada bahasa-bahasa yang dituturkan di Kabupaten Banyumas. Penelitian ini juga bertujuan mengetahui strategi komunikasi dan tingkat akomodasi masyarakat tutur di Kabupaten Banyumas. Selain itu, penelitian ini bertujuan mengidentifikasi keberagaman terhadap penggunaan bahasa Indonesia, bahasa daerah dan bahasa asing berdasarkan karakteristik responden di wilayah pakai di Kabupaten Banyumas. Tujuan lainnya yaitu mengidentifikasi komunitas sosial manakah dalam masing-masing masyarakat bahasa tersebut yang lebih dominan melakukan adaptasi linguistik sementara komunitas lainnya tidak dominan. Mengidentifikasi adakah perbedaan kecenderungan melakukan adaptasi linguistik di antara masyarakat tutur yang rentan terhadap konflik (disharmoni) dengan masyarakat tutur yang tidak rentan terhadap konflik social (harmoni). Pengumpulan data menggunakan teknik simak dan depth interview. Analisis data menggunakan model interaktif. Hasil penelitian ini menunjukkan bahwa terdapat tantangan adaptasi linguistik masyarakat tutur di Kabupaten Banyumas yang berkaitan dengan perbedaan bahasa, budaya dan gaya komunikasi yang ada dengan latar belakang yang berbeda. Kemudian, terdapat strategi adaptasi linguistik masyarakat tutur di Kabupaten Banyumas yang berkaitan dengan kompetensi komunikatif. Akomodasi bahasa masyarakat tutur Banyumas terhadap bahasa Indonesia sangat akomodatif, terhadap bahasa ibu juga akomodatif, tetapi terhadap bahasa daerah kedua dan bahasa asing tidak akomodatif.